Antioxidants and lipid peroxidation status in the blood of patients with psoriasis - Kökçam, I; Naziroglu, M (Elsevier Science Bv, 1999)
The aim of this research was to determine levels in blood of vitamin E, beta carotene, lipid peroxidation as malondialdehyde (MDA), reduced glutathione (GSH) and glutathione peroxidase (GSH-Px) activity in patients with psoriasis. Studies were carried out on 34 patients with moderate and severe psoriases and healthy age-matched controls. Red blood cell (RBC) and plasma samples from healthy and patient subjects were taken. Levels of GSH and the activity of GSH-Px in both plasma and RBC samples were significantly (P < 0.001) lower in patients with psoriasis than in controls, whereas beta carotene levels in plasma and MDA levels in RBC samples were significantly (P < 0.01, P < 0.001) higher in patients with psoriasis than in controls. However, vitamin E and MDA levels in plasma did not differ statistically. Although being far from conclusive, these results provide some evidence for a potential role of increased lipid peroxidation and decreased antioxidants in psoriasis. (C) 1999 Published by Elsevier Science BN. All rights reserved.
Keywords: psoriasis; lipid peroxidation; antioxidants; vitamin E; beta carotene